Improving the use of research evidence in guideline development: 8. Synthesis and presentation of evidence - Fretheim Atle; Schünemann Holger J; Oxman Andrew D (BMC, 2006)
Abstract Background The World Health Organization (WHO), like many other organisations around the world, has recognised the need to use more rigorous processes to ensure that health care recommendations are informed by the best available research evidence. This is the eighth of a series of 16 reviews that have been prepared as background for advice from the WHO Advisory Committee on Health Research to WHO on how to achieve this. Objectives We reviewed the literature on the synthesis and presentation of research evidence, focusing on four key questions. Methods We searched PubMed and three databases of methodological studies for existing systematic reviews and relevant methodological research. We did not conduct systematic reviews ourselves. Our conclusions are based on the available evidence, consideration of what WHO and other organisations are doing and logical arguments. Key questions and answers We found two reviews of instruments for critically appraising systematic reviews, several studies of the importance of using extensive searches for reviews and determining when it is important to update reviews, and consensus statements about the reporting of reviews that informed our answers to the following questions. How should existing systematic reviews be critically appraised? • Because preparing systematic reviews can take over a year and require capacity and resources, existing reviews should be used when possible and updated, if needed. • Standard criteria, such as A MeaSurement Tool to Assess Reviews (AMSTAR), should be used to critically appraise existing systematic reviews, together with an assessment of the relevance of the review to the questions being asked. When and how should WHO undertake or commission new reviews? • Consideration should be given to undertaking or commissioning a new review whenever a relevant, up-to-date review of good quality is not available. • When time or resources are limited it may be necessary to undertake rapid assessments. The methods that are used to do these assessments should be reported, including important limitations and uncertainties and explicit consideration of the need and urgency of undertaking a full systematic review. • Because WHO has limited capacity for undertaking systematic reviews, reviews will often need to be commissioned when a new review is needed. Consideration should be given to establishing collaborating centres to undertake or support this work, similar to what some national organisations have done. How should the findings of systematic reviews be summarised and presented to committees responsible for making recommendations? • Concise summaries (evidence tables) of the best available evidence for each important outcome, including benefits, harms and costs, should be presented to the groups responsible for making recommendations. These should include an assessment of the quality of the evidence and a summary of the findings for each outcome. • The full systematic reviews, on which the summaries are based, should also be available to both those making recommendations and users of the recommendations. What additional information is needed to inform recommendations and how should this information be synthesised with information about effects and presented to committees? • Additional information that is needed to inform recommendations includes factors that might modify the expected effects, need (prevalence, baseline risk or status), values (the relative importance of key outcomes), costs and the availability of resources. • Any assumptions that are made about values or other factors that may vary from setting to setting should be made explicit. • For global guidelines that are intended to inform decisions in different settings, consideration should be given to using a template to assist the synthesis of information specific to a setting with the global evidence of the effects of the relevant interventions.